Teacher Learning with Classroom Assessment Perspectives from Asia Pacific (Springer Singapore, 2018)
This book discusses the interwoven themes of teacher learning and classroom assessment, highlighting the complexity and intricacy of these processes in a range of very different classroom contexts. The case studies demonstrate how classroom assessment is needed for teachers to learn about teaching and for them to be able to grow professionally and improve student learning. Although this volume is mainly situated in the unique and varied contexts of the Asia-Pacific region, it addresses the key issues of quality teaching, assessment, and accountability in a global context.